A handbook for teaching assistants : teachers and assistants working together - Fox, Glenys (b, 2017)
This new edition provides essential guidance for all teaching assistants, especially those who are new to the job, and to the teachers working with them. Glenys Fox details the roles and responsibilities of the teaching assistant as well as providing helpful advice on how to best support the teacher, the pupil, the curriculum and the school. This practical handbook will bring experienced TAs up to date on changes to National educational guidance, including changes in the National Curriculum, assessment, and the Special Educational Needs framework. This text enables the assistant and the teacher to work together more effectively in supporting and promoting the progress of children and young people
Includes bibliographical references.
Keywords: Teachers' assistants -- Great Britain -- Handbooks, manuals, etc; Special education -- Great Britain -- Handbooks, manuals, etc